P-788 A proof-of-concept study evaluating the effect of personalized dosages of follitropin delta in intra-uterine insemination (IUI): Personalized IUI Treatment Study (PITS). (30th June 2022) - Minano, J; Hemmings, R; Phillips, S; Bissonnette, F; Kadoch, I.J
Abstract: Study question: Would a personalized dosing regimen of follitropin delta based on AMH and body weight allow better management of women's IUI cycle? Summary answer: A personalized regimen of follitropin delta based on AMH and body weight has increased pregnancy rate without having increased multiple pregnancies in our studied population. What is known already: IUI has been widely used as a common treatment for infertile couples due to its simplicity and low cost. Some studies have shown that cumulative live birth rate (LBR) can be increased by use of controlled ovarian stimulation. A recent meta-analysis reported that a protocol based on exogenous gonadotropins increases the LBR. Hence, this technique remains a treatment option reaching a LBR ranging from 8.5 to 12.2%. Nevertheless, this increase in LBR is associated with a non-negligible rate of adverse events, including ovarian hyper-stimulation syndrome (OHSS) and multiple pregnancies (7.2% - 9% of twins and 0.4% - 0.5% of triplets). Study design, size, duration: This prospective, phase 2, open-label study enrolled 110 women 18 - 42 years of age from January 2020 to January 2021. Participants had received up to 3 IUIs. The primary efficacy variable was the number of cycles where target number of 2 or 3 mature follicles (MII) were reached. The secondary objective and safety variable were the incidence of cycle cancellations, the clinical pregnancy rate and the proportion of multiple pregnancies over 3 consecutive cycles. Participants/materials, setting, methods: Follitropin delta dosing algorithm is modeled to achieve 8-14 oocytes in IVF cycles. To achieve 2-3 mature follicles, the algorithmically derived dose was divided by 4. Follitropin delta adjustment for subsequent IUIs were based on number of MII at previous IUI and age. Dose modification was made when excessive or no response were observed at stimulation day 8 during ultrasound monitoring. If urine pregnancy test was positive, a viability ultrasound was prescribed at 6-8 weeks. Main results and the role of chance: Descriptive statistics were used in this proof-of-concept study. The mean age of all subjects was 34.46 years (± 4.5). The mean weight was 69.2 kg (± 11.24), AMH - 3.84 ng/ml (± 13), FSH - 6.3 IU (± 2.61), antral follicular count - 15 (± 8.6). The mean number of years of infertility was 2.48 ± 3.57. The percentage of patients who obtained 2 or 3 follicles during the 3 consecutive IUI was 34%, 37% and 47% respectively. The percentage of patients who reached ≥3 follicles was 1.9%, 0% and 1.4% respectively, demonstrating the ability of the proposed dosing regimen to achieve the desired goal. The percentage of cycle cancelation was stable throughout the 3 cycles: 8.5%, 2.4% and 8.8% respectively. Only 6 multiple pregnancies over 40 clinical pregnancies (15%) were observed, showing the proposed dosing regimen's safe approach. The cumulative clinical pregnancy rate over the 3 cycles among patients completing the study was 37.7%, and the cumulative live birth rate (calculated ad hoc, as it was not part of the study protocol) was 33%, leading to the personalized dosing regimen proposed in this study to be considered for use in clinical practice. Limitations, reasons for caution: The study's limitations are its exploratory nature, open-label design and small sample size. Wider implications of the findings: PITS study is the first one using follitropin delta for stimulation in intra-uterine insemination. It confirms the initial hypothesis of a potential benefit of a personalized dosing regimen of follitropin delta. A larger, randomized controlled study will be needed to confirm these initial findings. Trial registration number: NCT03830723